Constitutional Protection of Gig workers' Right to Occupational Safety: Analysis of Legal Vacuum and State Obligations in the Digital Economy Era - Dibi Vation Manik; Tamaulina Br. Sembiring; Ismaidar Ismaidar (Journal of Research in Social Science and Humanities, 2025)
Development rapidly Indonesia's digital economy has cause increasing amount Gig workers facing risk significant related health and safety work . Ambiguity specific laws and regulations has create a situation where Gig workers are mostly big No protected . Analysis normative This investigate right constitutional related safety Work for Gig workers , evaluating mismatch between directions constitutional and action existing regulations , as well as provide solution suggestions relevant laws with gig economy . Descriptive-analytical techniques qualitative used , with refers to the material primary, secondary , and tertiary laws . Research results show that right on decent living and shelter in place Work in accordance with The 1945 Constitution has not fully implemented for Gig workers . Challenges systemic — such as ambiguous legal status , inadequate oversight adequate , and laws rigid employment — hinders implementation effective protection . Research This emphasize importance revise policy employment to be more inclusive , developing system guarantee flexible social , and create steps enforcement solid law For fulfil not quite enough answer constitutional state. In special study This highlight that change laws and policies innovation is very important For protect rights Gig workers and ensure environment safe and dignified work in Indonesia's digital economy